Functional traits and environment jointly determine the spatial scaling of population stability in North American birds. Issue 4 (6th February 2023) - Hong, Pubin; Li, Zhouyuan; Yang, Qi; Deng, Wanlu; Xu, Yanjie; Tobias, Joseph A.; Wang, Shaopeng
Abstract: Understanding the spatial scaling of population stability is critical for informing conservation strategies. A recently proposed metric for quantifying how population stability varies across scales is the invariability–area relationship (IAR), but the underlying drivers shaping IARs remain unclear. Using 15‐year records of 249 bird species in 1035 survey transects in North America, we derived the IAR for each species by calculating population temporal invariability at different spatial scales (i.e., number of routes) and investigated how species IARs were influenced by functional traits and environmental factors. We found that species with faster life history traits and reduced flight efficiency had higher IAR intercepts (i.e., locally more stable), whereas migratory species exhibited higher IAR slopes (i.e., a faster gain of stability with increasing spatial scale). In addition, spatial correlation in temperature and vegetation structure synchronized bird population dynamics over space and thus decreased IAR slopes. By demonstrating the joint influence of functional traits and environmental factors on bird population stability across scales, our results highlight the need for dynamic conservation strategies tailored to particular types of species in an era of global environmental changes.